(untitled) (Journal of Economic Research & Business Administration, 2024)
The world experience shows many successful cases of the development of special economic zones. Effective governmental regulations on this matter are crucial for creating a favorable infrastructure and reducing administrative barriers for investors. Accordingly, this article explores and analyzes the public administration tools in terms of governance of special economic zones of Kazakhstan, Russia and Kyrgyzstan. The aim of the research is provision of secondary data analysis of the effectiveness of governance in three countries. The evaluation and reviewing legislation, statistics, and publications related to the functionality of zones were used by the authors. According to the results, less attractive conditions for investors have been found in Kyrgyzstan and it could be possible due to weak public administration. The findings show that there is only one fully functioning special economic zone in Kyrgyzstan, and the effectiveness and advantage to the country’s economy is not so significant. The results reveal that the low level of proper incentives for investors or factors of state regulations and public administration could be the reason for the functioning of only one SEZ in Kyrgyzstan. It is concluded that, despite differences in the vision and objectives of SEZ formation in Russia, Kazakhstan, and Kyrgyzstan, governmental regulations directly affect the performance and prosperity of the zones. The results of this research could be used among practitioners, academia and policymakers by providing knowledge that could lead to better understanding of the functionality, governance and the level of effectiveness of SEZ in Kazakhstan, Russia and Kyrgyzstan. Key words: public management, special economic zones, effectiveness, performance, state regulations, investments, development.